Sokolow‐Lyon voltage is suitable for monitoring improvement in cardiac function and prognosis of patients with idiopathic dilated cardiomyopathy. Issue 5 (3rd February 2017) - Fukaya, Kenji; Takeshita, Kyosuke; Okumura, Takahiro; Hiraiwa, Hiroaki; Aoki, Soichiro; Ichii, Takeo; Sugiura, Yuki; Kitagawa, Katsuhide; Kondo, Toru; Watanabe, Naoki; Kano, Naoaki; Furusawa, Kenji; et al.
Abstract : Background: The clinical significance of electrocardiogram in the assessment of patients with idiopathic dilated cardiomyopathy (IDCM) is currently unknown. The aim of this study was to determine the feasibility of recording serial changes in Sokolow–Lyon voltage (∆%QRS‐voltage) in one year to estimate left ventricular reverse remodeling (LVRR) and predict a prognosis of IDCM patients under tailored medical therapy. Methods: Sixty‐eight consecutive patients with mild symptoms (52.1 ± 13 years old; 69% men; NYHA I/II/III/IV; 33/29/6/0) underwent electrocardiography and echocardiography at baseline and 12 month follow‐up (follow‐up period: 3.9 years). Results: LVRR was observed in 30 patients (44.1%). The ∆%QRS‐voltage was significantly lower in the LVRR group (LVRR; −26.9%, non‐LVRR: −9.2%, p  < .001). Univariate analysis showed that ∆%QRS‐voltage correlated with ∆%LV end‐diastolic diameter (r = .634, p  < .001), and with ∆%LV ejection fraction and ∆%LV mass index (r = −.412, p  < .001; r = .429, p  < .001 respectively). Using receiver operating characteristic curve analysis for the estimation of LVRR, ∆%QRS of −14.7% showed optimal sensitivity (63.2%) and specificity (83.3%) (AUC = 0.775, p  < .001). The composite endpoints of cardiac death ( n  = 0), hospitalization for advanced heart failure ( n  = 11) and fatal arrhythmia ( n  = 2) were observed in 13 patients during the follow‐up period. Kaplan– Meier analysis showed significantly higher event‐free rate in patients of the low ∆%QRS‐voltage group (<−14.7%) (83%) than those of the high group (66%, p  = .022). Conclusions: The present study showed that decrease in Sokolow–Lyon voltage is associated with improvement in cardiac function and favorable prognosis in IDCM patients on medical therapy, suggesting that this index is a feasible marker for response to treatment of IDCM.